The Inquiry-Based Teaching To Improve The Students' Reading Comprehension (A Classroom Action Research at SMP MTA Gemolong at IX Grade 2011/2012 Academic Year) - Kumalasari, Fajriyah (2012)
This thesis is written to improve the students reading comprehension by Inquiry Based Teaching. The objectives of the research are to know whether or not inquiry based teaching can improve the students' reading comprehension, is observe the strengths and the weaknesses of inquiry based teaching and learning when it is applied to improve students' reading comprehension. The research was conducted at SMP MTA Gemolong from Feb, 2011 till April, 2012. The subjects of the research include thirty one students of class nine (IX). In collecting the data, the researcher used observation notes, photograph, interview, and presentation assessment. To analyze the qualitative, the researcher applied the students participation in class was observed and noted in form of description as suggested by Baxter. And to analyze the quantitative data, it was used presentation assessment which taken from Yulia (2005) which is adapted from the performance criteria by Hughes (1989: 113). The research findings shows that,(1) inquiry based teaching is effective to improve the students' reading comprehension in class. That can be seen from their behavior during the teaching learning process. (2) the strength of the strategy include (a) the improvement of the students mastery of reading text, (b) the change of attitude and conflict management, (c) the raising of motivation and interest, (d) the improvement of vocabulary, (e) leadership values, (f) the improvement of students' skill of report text, (g) the improvement of students' mastery of grammar and micro skills for reading, (h) the establishment of selfconfidence and trustworthiness, and (i) the establishment of cooperation and collaboration and social values. (j) the improvement of the students' report text, (k) the improvement of making use of information technology, (l) emotional therapy. Whereas (3) the weaknesses are, (a) the students could not manage the time well and effectively. (b) the students used English in discussion but sometimes their grammar was not correct or even they could not express their idea. (c) the students' vocabulary was poor.